Immersive installation of proverbs for the hearing impaired - Nur Faqihah Adnan; Syarmila Hany Haron (ARTEKS : Jurnal Teknik Arsitektur)
Proverbs is a folklore known as oral tradition and has been handed down orally from generation to generation. Proverbs are vital in Malay culture, regulating people's lives and containing history, advice, life lessons and education. Due to the passage of proverbs orally in past years, the main issue in this paper is to make people with hearing impairment feel included and better understand the meaning behind Malay Proverbs. This paper emphasises the potential of immersive installation to bridge the gap, ensuring accessibility for all users and fostering greater community engagement while appreciating Malay Proverbs. Immersive installations often include noise elements, tactile experiences, vibrations, and scents. This research has two objectives: (1) to examine that proverbs are effectively communicated and understood by hearing-impaired individuals through immersive technology and (2) to analyse space design principles for the hearing-impaired community. This study's research method is a qualitative study that identifies the aims and suggestions based on data acquired from literature reviews, gaps in the literature, case studies, and observations. Through this research, it may contribute to the development of inclusive and accessible environments for the hearing impaired while also advancing the understanding of Malay Proverbs.